STRATEGI PENANGANAN RISIKO OPERASIONAL PEMASARAN PRODUK TEH CELUP HIJAU WALINI PADA INDUSTRI HILIR TEH PT PERKEBUNAN NUSANTARA VIII, BANDUNG, JAWA BARAT - Idzhar Jaya Nugraha; Akhmad Riyadi Wastra; Lilis Imamah Ichdayati (AGRIBUSINESS JOURNAL, 2017)
Tea is an Indonesian excellent product that has been recognized worldwide. Indonesia is the seventh best tea producer which have international market potential.Therefore Tea Indonesia is expected to take advantage on existing opportunities from downstream industry of tea. The one of stated-owned plantation company who have downstream industry of tea is PT Perkebunan Nusantara VIII. Walini’s tea is a one famous brand product for this company. The development downstream industry of tea PTPN VIII is faced with yet achieved the expected sales. Amount of cost operational marketing and sales are indicated of operational risk. The objective of this study is strategy handling of marketing operational risk Walini Green tea bag product in downstream industry of tea PTPN VIII. Identification risk is first step to know the problem of marketing operational in downstream industry of tea PTPN VIII. By using Z-Score and Value at Risk (VAR) metode, it be showed the result of probability and impact of marketing operational risk. Preventif and mitigation strategy can be handling this company to growth up the expected sales.